Do Airbnb's "Superhosts" deserve the badge? An empirical study from China. Issue 4 (3rd April 2019) - Sun, Nan; Liu, Dongsheng; Zhu, Anding; Chen, Yahui; Yuan, Yufei
ABSTRACT: The "Superhost" badge is that Airbnb entitles the host provides good services. This study verifies Airbnb's "Superhost" mechanism by applying text mining technologies, combined with Long Short-Term Memory (LSTM) and K -Means, to the entire dataset of tourists' online reviews of Hangzhou city, China. Six kinds of hosts' good services are identified, including "Three Meals or Night Snacks, " "Fruits, Drinks or Snacks, " "Travel Guides, " "Free Shuttle or Helping with Luggage, " "Chats, " and "Replies or Communications." The study reveals the minority of "Superhosts" are mentioned of providing the majority of six kinds of good services, which means "Superhosts" do deserve the badge.